Sleep quality among sample of Egyptian patients with Alzheimer’s disease: risk factors and role of genetic profiling for ACE, ACE 2 and APO E genotypes - Khaled Ahmed Elbeh; Mohamed Abdala Abbas; Mohammed H. Hassan; Mohamed Moslem Hefny; Shimaa Fathy Sakr; Reham Bakry Mohamed; Mahmoud Ahmed Bekiet; Tarek Desoky (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery, 2025)
Abstract Background Most individuals having Alzheimer’s disease generally experience increased frequency of awakenings as well as prolonged wakefulness periods at night. Brain wave research indicate reductions in both REM (dreaming stage) along with NREM (non-dreaming stage). The inherited pattern of Alzheimer’s disease is attributed to presence of genetic polymorphisms. The association of these polymorphisms and sleep pattern in Alzheimer’s disease patients was not assessed before. Purpose This research was aimed at assessing the association between sleep quality as well as genetic polymorphisms of ACE, ACE2 and Apo E among Alzheimer’s disease patients in Upper Egypt. Patients and methods Our cross-sectional study with analytic component involved 50 cases having Alzheimer’s disease evaluated utilizing Pittsburg sleep quality index for sleep quality. They were accordingly divided into good as well as poor sleep quality groups. Genetic analysis of ACE, ACE2 (rs2285666) SNPs and Apo E (rs121918398) SNPs was done using (RFLP-PCR) I. Results No statistically significant variation was documented among both groups regarding age as well as age at diagnosis. Female patients were more susceptible for poor sleep quality. In addition, patients came from rural areas were significantly higher among poor sleep quality group. Statistical significant variations were documented among both groups as regard presenting symptoms and HAM-A and HAM-D. No statistically significant variations were documented among both groups as regard ACE genotypes; however, ACE 2 AA genotype and A allele were higher with statistically significant difference among poor sleep quality group. Apo E3/E4 genotype and E4 allele were greater with statistically significant variations among poor sleep quality group. Conclusions Female patient and rural Alzheimer’s disease patients at high risk for poor sleep quality. In addition, Apo E4 carriers and ACE2 AA carriers are at increasing susceptibility for poor sleep quality.